Association of seed colour with germination, physical and physiological growth of oil palm (Elaeis guineensis) seedlings - M. G., Norsazwan; U. R., Sinniah; A. B., Puteh; P., Namasivayam; D. R., Appleton; M., Mohaimi; I. A., Aminuddin (Malaysian Palm Oil Board, 2022)
In commercial Dura x Pisifera (DxP) seed production, white-coloured seeds are perceived as abnormal despite lack of scientific evidence to support this. This study evaluates different seed colour (black, semiwhite and white) during germination and nursery evaluation. Four replications of 10 seeds were used for the evaluation of seed characteristic. Seed germination was conducted using four replications of 100 seeds by subjecting the seeds to 60 days of heat-treatment followed by germination at 30ºC. Thirty pre-germinated DxP seeds per replication were then transferred into the nursery for morphological, physiological and growth assessment at three months interval until 12 months after sowing. Germination test shows all seed types indicated similar germination percentage (more than 78%) and speed (13-15 days of mean germination time). Nursery assessment shows black seed indicated higher overall biomass within the first three months, however, no differences in growth were observed from six until 12 months after sowing. Physiological evaluation including net photosynthesis (5.3-18.13 µmol CO2 m–2 s–1), stomatal conductance and transpiration rate were similar among the seedlings produced by seeds differing in colour. Hence, seed colour does not implicate abnormality and should not be discarded for the purpose of seed production.